English Lingua-Cultural Paradigmatic Views Held by Indonesian EFL Teachers - Morganna, Ruly; Eka Apriani; Dadan Supardan (Corolla International Conference, 2023)
The aim of this study was to investigate the views of Indonesian EFL teachers on lingua-culture and its representation in EFL instruction. The study employed an instrumental case study approach and involved 10 EFL teachers from Indonesia who were interviewed using a semi-structured format. The findings revealed that eight of the teachers held an essentialist perspective, considering lingua-culture as a single language with one culture. They emphasized native-like proficiency, natively authentic materials, communicative competence theory, and indirect cultural instruction. However, the remaining two teachers adhered to a non-essentialist philosophy and viewed lingua-culture as a single language with multiple cultures, emphasizing cross-cultural non-native English materials, intercultural communicative competence, and direct cultural instruction. Considering the diversity among Indonesian students, this study recommends that EFL teachers adopt a non-essentialist approach to ensure the long-term sustainability of EFL instruction. Additionally, the study proposes two conceptual frameworks for EFL lingua-culture paradigms, with only one found to be suitable for the diversity of Indonesian students based on empirical evidence.